Ownership Dispute Resolution Brand Ownership Rights In Indonesia - Dodi Rusmana; Bintan R. Saragih; Simona Bustani (Pusat Publikasi Nusantara, 2023)
Brand rights are one part of intellectual property rights that have an important role in the business world of trading of goods and services, especially in maintaining healthy business competition. The research method in this writing uses a normative juridical type of research. Normative legal research is also called literature law research. The approach used in this study is the Statue Approach method. The results of this research include the settlement of brand disputes can be resolved in two ways, namely through litigation and non-litigation. Judges are expected to have the ability to translate the values of justice in matters faced by him through his decisions. Settlement of trademark disputes in court is expected to be guided by the principles of justice, so that the settlement of trademark disputes can create legal certainty. Lawsuits in court or alternative dispute resolution such as arbitration. Furthermore, the legal implication for the decision may be to regulate